2018
DOI: 10.1038/s41467-018-07019-x
|View full text |Cite
|
Sign up to set email alerts
|

A low-gluten diet induces changes in the intestinal microbiome of healthy Danish adults

Abstract: Adherence to a low-gluten diet has become increasingly common in parts of the general population. However, the effects of reducing gluten-rich food items including wheat, barley and rye cereals in healthy adults are unclear. Here, we undertook a randomised, controlled, cross-over trial involving 60 middle-aged Danish adults without known disorders with two 8-week interventions comparing a low-gluten diet (2 g gluten per day) and a high-gluten diet (18 g gluten per day), separated by a washout period of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 76 publications
6
126
0
8
Order By: Relevance
“…We recently found that urine levels of enterolactone‐glucuronide increased following a low‐gluten diet (matched in total dietary fibre) compared with a high‐gluten diet (Hansen et al . ). Thus, microbial production of enterolactone may not only depend on the amount of dietary fibre but also on the type of dietary fibre.…”
Section: Diet‐derived Microbial Metabolites In Health and Diseasementioning
confidence: 97%
See 3 more Smart Citations
“…We recently found that urine levels of enterolactone‐glucuronide increased following a low‐gluten diet (matched in total dietary fibre) compared with a high‐gluten diet (Hansen et al . ). Thus, microbial production of enterolactone may not only depend on the amount of dietary fibre but also on the type of dietary fibre.…”
Section: Diet‐derived Microbial Metabolites In Health and Diseasementioning
confidence: 97%
“…Other examples of dietary manipulations resulting in observable microbiome changes include adoption of a low‐gluten diet (containing no dietary fibres from wheat, rye and barley; Hansen et al . ) or a low‐FODMAP diet (restricted in fermentable oligo‐, di‐, monosaccharides and polyols; Halmos et al . ; Staudacher et al .…”
Section: Diet Shapes the Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…Linear discriminant analysis Effect size (LEfSe) was performed to identify differences in the microbial structure between groups, with the default parameter. 25 PICRUSt was used to identify differences in the metabolic pathways between each group against the KEGG. 26 Redundancy analysis (RDA) was performed by using "vegan" and "ggplot2" package of R. 22,23 The length of arrow represents the constraint effect of different environmental variables exerted on sample distribution in two-dimension.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%